System reliability-based limit state design of support scaffolding systems. (1st August 2020) - Wang, Cao; Zhang, Hao; Rasmussen, Kim J.R.; Reynolds, James; Yan, Shen
Highlights: A reliability-based limit state design approach is developed for support scaffolding systems. A stochastic FE method is used to analyse the ultimate load-carrying capacities. The latest construction load survey data is utilized in developing the new design criteria. Abstract: The safety of scaffold systems during construction is vital to prevent failures with catastrophic consequences. Engineering practice in the scaffolding industry, however, does not have a rational structural reliability basis as that used for buildings and bridges. The implementation of design clauses for scaffold systems in the current standards partially relies on judgement suffering from the lack of data. With this regard, a reliability-based limit state design approach is developed in this study, making full use of the advanced finite element (FE) method and the recently accumulated statistical data of scaffolding resistance and construction loads. A stochastic finite element method is used to obtain the probabilistic characteristics of the ultimate load-carrying capacities of typical scaffolding frames, accounting for the uncertainties associated with structural geometry, material and stiffness properties. The latest construction load survey data is utilized. System reliability assessment is then performed to develop new design criteria which are consistent with generally accepted structural reliability targets.